2012
DOI: 10.1038/gene.2012.44
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent variation of genotypes in MHC II transactivator gene (CIITA) in controls and association to type 1 diabetes

Abstract: The major histocompatibility complex class II transactivator (CIITA) gene (16p13) has been reported to associate with susceptibility to multiple sclerosis, rheumatoid arthritis and myocardial infarction, recently also to celiac disease at genome-wide level. However, attempts to replicate association have been inconclusive. Previously, we have observed linkage to the CIITA region in Scandinavian type 1 diabetes (T1D) families. Here we analyze five Swedish T1D cohorts and a combined control material from previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…CIITA has been implicated in immune function through association with autoimmune diseases or very recently with leprosy (Liu et al 2015). The gene complex including CIITA and neighboring DEXI/CLEC16A has been shown to be associated with multiple autoimmune diseases (Bronson et al 2011; Gyllenberg et al 2012, 2014; Leikfoss et al 2015). DOCK2 is predominantly expressed in hematopoietic cells, regulates migration and activation of neutrophils through Rac activation (Nishikimi et al 2013) and is associated with early-onset invasive infections (Dobbs et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…CIITA has been implicated in immune function through association with autoimmune diseases or very recently with leprosy (Liu et al 2015). The gene complex including CIITA and neighboring DEXI/CLEC16A has been shown to be associated with multiple autoimmune diseases (Bronson et al 2011; Gyllenberg et al 2012, 2014; Leikfoss et al 2015). DOCK2 is predominantly expressed in hematopoietic cells, regulates migration and activation of neutrophils through Rac activation (Nishikimi et al 2013) and is associated with early-onset invasive infections (Dobbs et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…GWAS and patient exome sequencing studies have linked SNPs in CIITA to celiac disease (238, 239), susceptibility to myocardial infarction (240), rheumatoid arthritis (240242), multiple sclerosis (240, 242), primary adrenal insufficiency (243), SLE (244), and type 1 diabetes (245, 246), although these results have not always been replicated in subsequent studies (247249). Gyllenberg et al suggested that age-dependent variation in the gene encoding CIITA could be responsible for false associations in GWAS (250).…”
Section: Non-inflammasome-forming Nlrsmentioning
confidence: 99%
“…41 Chromosomal translocation of CIITA has been linked to primary mediastinal B-cell lymphoma and classical Hodgkin lymphoma. 42 Genetic variations in the CIITA gene have also been associated with several autoimmune disorders in humans, including RA, 13,15,16 MS, 13,17,18 myocardial infarction, 13 T1D, 19 coeliac disease 20 and systemic lupus erythematosus. 20,21 Different SNPs have been associated with these diseases, including rs3087456 in the type III promoter of CIITA, an intronic SNP rs8048002, and rs4774, which is a missense mutation resulting in an amino acid change from glycine to alanine.…”
Section: Discussionmentioning
confidence: 99%
“…13 It was later shown in the congenic strains in rats that the C2ta polymorphisms alter susceptibility to experimental autoimmune encephalomyelitis (EAE), a chronic relapsing model of MS. 14 The experimental findings in rats prompted further investigation of C2TA in humans and it was demonstrated that a single nucleotide polymorphism in the 5 0 flanking region of type III promoter of C2TA is associated with susceptibility to RA, MS and myocardial infarction. 13 C2TA disease association has since then been shown in different patient cohorts in not only RA 15,16 and MS, 17,18 but also T1D, 19 coeliac disease 20 and systemic lupus erythematosus, 21,22 although disease associations could not be reproduced in some populations. [23][24][25] In this study, we generated a C2ta congenic mouse strain to investigate the effect of an allelic variant of C2ta promoter on MHC-II expression in different antigen-presenting cells (APCs).…”
Section: M M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 99%
See 1 more Smart Citation